(untitled) - Adkins, Mary (New York, NY, 2019)
"After PR power Iris Massey dies from a terminal illness at age 33, friend and colleague Smith learns that in her final months she created a blog full of acute observations on a life cut short. He wants to publish it, but that will require the cooperation of Iris's despairing chef sister, Jade"--Publisher's description.
Keywords: Publishers and publishing; Fiction; Friendship; Fiction; Interpersonal relations; Fiction; Epistolary fiction